Bifunctional Janus microparticles with spatially segregated proteins - Tang, Jennifer L. (2012)
We present a fabrication process to create bifunctional microparticles displaying two distinct proteins that are spatially segregated onto the surface hemispheres. Silica and polystyrene microparticles with 2.0 μm, 4.1 μm, and 4.7 μm diameters are processed with metal deposition to form two chemically distinct and segregated hemispheres. The surface of each hemisphere is then separately derivatized with biological proteins using different chemical conjugation strategies. These bifunctional Janus particles possess biologically relevant, native conformation proteins attached to a biologically-unreactive and safe substrate. They also display high densities of each type of proteins which may enable a range of capabilities that monofunctional particles cannot, such as improved targeting of drugs and bioimaging agents.